Why Agriculture Productivity Falls The Political Economy of Agrarian Transition - Titumir, Rashed (Purdue University Press, 2023)
The book offers a new explanation of the decline in agricultural productivity in developing countries. It transcends the conventional approach to understanding productivity using factors of production. It employs the role of formal and informal institutions that govern transactions, property rights and accumulation among farm-holder communities, and seeks to understand agricultural productivity using both new and conventional variables, using a combined ethnographic and empirical methodology. The book engages with the debate on the market and non-market forces driving agrarian transition and advances that the agrarian transition be understood in relation to the wider (non-agrarian) economic development in society, as political settlement and primitive accumulation permit (inhibit) property rights being re-allocated in growth-enhancing directions. It also demonstrates that the existing process of accumulation prevents sustainable agriculture because of market failures caused by weak institutions, resulting in arrested productivity growth.